2018
DOI: 10.17756/jfcn.2018-060
|View full text |Cite
|
Sign up to set email alerts
|

Functional Oligosaccharide: Chemicals Structure, Manufacturing, Health Benefits, Applications and Regulations

Abstract: Functional oligosaccharides are carbohydrates that have two to ten monosaccharides units linked together with glycosidic bonds. The two linked monosaccharides (disaccharides) of maltose, sucrose, and lactose are digestible oligosaccharides by human gut enzymes. These, digestible disaccharides are sugars and are not classified as functional oligosaccharides. Functional oligosaccharides are non-digestible by human gut enzymes and providing health benefits as fibers and prebiotics [1]. The common known functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 50 publications
1
47
0
3
Order By: Relevance
“…In the current study we observed an increase in total soluble sugars and reductions in glucose and fructose in the stored corn which were in concordance with the ndings of Paraginski [5]. We observed that higher oligosaccharide and lower monosaccharide contents in stored corn could bene t gut health [35].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study we observed an increase in total soluble sugars and reductions in glucose and fructose in the stored corn which were in concordance with the ndings of Paraginski [5]. We observed that higher oligosaccharide and lower monosaccharide contents in stored corn could bene t gut health [35].…”
Section: Discussionsupporting
confidence: 91%
“…Studies on the bioconversion of plant lignans to enterolignans in the human gut were reported with various plants lignans, such as secoisolariciresinol and sesaminol [27,28]. Previous studies on the use of fructo-oligosaccharides as prebiotics showed several beneficial effects, including improving mineral absorption, decreasing serum cholesterol and triglycerides, and enhancing the growth of beneficial bacteria in the colon [29]. These reports suggest that intake of Omija beverages fermented with fructo-oligosaccharide can afford further health benefits.…”
Section: Lignan Content In Omija Beverages and Drink From S Chinensimentioning
confidence: 99%
“…The accepted daily intake of another class of prebiotics, fructooligosaccharides, should not be higher than 20 g/day for adults, and 4.2 g/day for infants younger than 1 year of age (Ten Bruggencate, Bovee-Oudenhoven, Lettink-Wissink, Katan, & van der Meer, 2006), because of side effects such as intestinal gas (flatulence), intestinal noises, bloating stomach cramps, and diarrhea (Osama, 2018). In a study by Lewis, Burmeister, and Brazier (2005) in 142 patients 18 years and older with Clostridium difficile-induced diarrhea, daily consumption of 12 g of oligofructose compared to placebo reduced the incidence of diarrhea.…”
Section: Functionsmentioning
confidence: 99%